(untitled) (Global Journal of Computer Science and Technology, 2019)
The mathematical definition of the System is proposed on based from different and above all humanitarian sources. This definition a prerequisite for the creation of the mathematical apparatus of the Systems and particulare the Control Systems wich are submit to him. A non algorithmic (i.e.mathamatical) language of logic and actions has been created for Systems. Their informativity is result of the application of the systems definition.